The use of modern devices and human activity today have increased noise problem. The applicaton of acoustic panels in building construction could be as an alternative to overcome this problem. The purpose of this study was to investigate acoustical properties of sound absorption coefficient and sound transmission loss from wood wool or excelsior board. Three fast growing species, sengon (Paraserianthes falcataria), african wood (Maesopsis eminii), and mangium (Acacia mangium) lumbers were proces - Lina KARLINASARI; Dede HERMAWAN; Akhiruddin MADDU; Bagus MARTIANTO (Jurnal Ilmu dan Teknologi Hasil Hutan, 2011)
The use of modern devices and human activity today have increased noise problem. The applicaton of acoustic panels in building construction could be as an alternative to overcome this problem. The purpose of this study was to investigate acoustical properties of sound absorption coefficient and sound transmission loss from wood wool or excelsior board. Three fast growing species, sengon (Paraserianthes falcataria), african wood (Maesopsis eminii), and mangium (Acacia mangium) lumbers were processed to obtain wool particles. Two different categories of board density and types of resins were used in this study. Sound absorption coefficient was determined using the impedance tube method, while that for the determination of transmission loss based on the reverberation room method. The results showed that the board density of 0.8 g/cm3 had good sound absorption for low and high frequencies compared with board of 1.0 g/cm3. In the medium frequencies those boards reflected the sound. Wood wool cement bonded board was good in sound absorption for high frequency. In the range low to high frequencies, the boards with isocyanate adhesive were good in transmission loss value compared with cement bonded boards. Meanwhile, the boards with density of 1.0 g/cm3 possessed transmission loss value higher than board of 0.8 g/cm3.   Keywords:     acoustic panel, wood wool board, fast growing species, sound absorption, transmission loss